2016
DOI: 10.1016/j.tjem.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The ED use and non-urgent visits of elderly patients

Abstract: ObjectiveTo evaluate the use of the emergency department (ED) by elderly patients, their non-urgent visits and the prevalence of main disease for ED visits.MethodsThis cross-sectional study was conducted on patients aged 65 years and over who visited the ED of a tertiary care university hospital in Turkey between January 2015 and January 2016 retrospectively.ResultsA total of 36,369 elderly patients who visited the ED were included in the study. The rate of ED visits by elderly patients was higher than their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
4
21
4
Order By: Relevance
“…Contrary to previous research which reported that a large proportion of all ED visits were presented during the day shift and the winter months 8,15,24 in our study similar to a study by Cigar from Turkey 25 , the highest proportion of ED visits was found during the working hours and the summer months. One explanation for this is that presentation in the ED during the working hours had a timely response to consultants and more easily available beds, but arrival to ED during the late hours may lead to delay in hospital admission because of excessive whole hospital occupancy for the said reasons.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Contrary to previous research which reported that a large proportion of all ED visits were presented during the day shift and the winter months 8,15,24 in our study similar to a study by Cigar from Turkey 25 , the highest proportion of ED visits was found during the working hours and the summer months. One explanation for this is that presentation in the ED during the working hours had a timely response to consultants and more easily available beds, but arrival to ED during the late hours may lead to delay in hospital admission because of excessive whole hospital occupancy for the said reasons.…”
Section: Resultscontrasting
confidence: 91%
“…In this present study, consistent with resents studies from Pakistan and Swiss 26,27 , the majority of older patients were male. But, studies from Turkey and other setting reported the majority of the older patients were female 15,23 . Such differences related to gender might be explained by reflects of social or regional variations in profiles of the older population where the research is carried out.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is important to understand why family functioning has become a critical issue when older patients and their families present at emergency departments (EDs). Older patients with complex care needs are frequent ED users compared to younger patients . Often, older patients arrive at the ED with a family member .…”
Section: Introductionmentioning
confidence: 99%
“…These changes increase the risk of trauma. Of those admitted to the emergency department because of trauma average 12% are >65 years (1)(2)(3). At the same time, 25%-28% of deaths in individuals aged ≥65 years are associated with trauma (4).…”
Section: Introductionmentioning
confidence: 99%